2020
DOI: 10.1088/1361-6382/abb39b
|View full text |Cite
|
Sign up to set email alerts
|

Superconformal indices at large N and the entropy of AdS5 × SE5 black holes

Abstract: The large N limit of the four-dimensional superconformal index was computed and successfully compared to the entropy of a class of AdS5 black holes only in the particular case of equal angular momenta. Using the Bethe ansatz formulation, we compute the index at large N with arbitrary chemical potentials for all charges and angular momenta, for general four-dimensional conformal theories with a holographic dual. We conjecture and bring some evidence that a particular universal contribution to the sum over Beth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(110 citation statements)
references
References 75 publications
5
103
0
1
Order By: Relevance
“…Under shifting by τ the argument of Z(u; ∆, τ ) we have the following property: 17) where the function Q k (u; ∆, τ ) measures the lack of periodicity of Z(u; ∆, τ ) in the variable u k under shifting by τ and is defined in [23] as:…”
Section: The Bethe-ansatz Formulation Of the Scimentioning
confidence: 99%
See 1 more Smart Citation
“…Under shifting by τ the argument of Z(u; ∆, τ ) we have the following property: 17) where the function Q k (u; ∆, τ ) measures the lack of periodicity of Z(u; ∆, τ ) in the variable u k under shifting by τ and is defined in [23] as:…”
Section: The Bethe-ansatz Formulation Of the Scimentioning
confidence: 99%
“…This solution was also used by Benini and Milan in their discussion of the SCI [3] and it was further extended in [15,16] where it was shown that it furnishes a solution for a generic class of N = 1 supersymmetric field theories. More recently, the BA approach to the index based on the basic solution was extended to include two different angular velocities [17], thus covering the most general type of asymptotically AdS 5 × S 5 black holes. Our results for the BA approach goes beyond the leading N 2 order in the large-N limit and takes the form I(τ ; ∆) = I(τ ; ∆) Basic BA + (contribution from other BA solutions)…”
Section: Jhep01(2021)001 1 Introduction and Summarymentioning
confidence: 99%
“…with the constraint ∆ 1 + ∆ 2 − τ − 1 − η 2 = 0 (which is derived from (5.4)). The overall constant κ is fixed as κ = 1 8 (see the discussion in [35]). The entropy is computed in terms of the charges Q 1,2 and angular momentum J of the dual black hole.…”
Section: Entropy Function and Dual Black Hole Entropymentioning
confidence: 99%
“…The BA approach has been introduced for a generic 4d N = 1 supersymmetric gauge theories in [28] based on insightful observations made in [29,30]. It was then applied to the N = 4 SU(N ) SYM theory with p = q in [3] and, more recently, to the same theory with p = h a and q = h b where a, b ∈ N and gcd(a, b) = 1 [31]. Some discussion of the BA approach to the SCI of a large class of 4d N = 1 supersymmetric quiver gauge theories was presented to leading order in [12,13] and a systematic sub-leading study was presented recently in [15].…”
Section: Review Of the Bethe-ansatz Approachmentioning
confidence: 99%